2014
DOI: 10.1097/pcc.0000000000000234
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of an Extracorporeal Cardiopulmonary Resuscitation Simulation Program Reduces Extracorporeal Cardiopulmonary Resuscitation Times in Real Patients*

Abstract: There are no standard guidelines of how a team should coordinate the efforts of nursing, physicians, extracorporeal membrane oxygenation specialists, surgeons, respiratory therapists, patient care technicians, and unit clerks to emergently execute this complex procedure. Because time is of the essence, it is essential to develop a highly functioning and well-coordinated team with a standardized method of the procedure, its documentation, and communication. Simulation accomplished this for our program. Followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 12 publications
2
53
0
Order By: Relevance
“…Multidisciplinary, high-fidelity, and serial simulation-based E-CPR training at Children’s National Health System reduced deployment time of ECMO in children with ongoing CPR after implementing an iterative in situ multidisciplinary simulation training program (44). The role of formal E-CPR training programs (both simulation and traditional) has yet to be fully elucidated in the current era, and our survey results confirm this notion as only half of respondents participate in simulation-based continuing education training for E-CPR.…”
Section: Discussionmentioning
confidence: 99%
“…Multidisciplinary, high-fidelity, and serial simulation-based E-CPR training at Children’s National Health System reduced deployment time of ECMO in children with ongoing CPR after implementing an iterative in situ multidisciplinary simulation training program (44). The role of formal E-CPR training programs (both simulation and traditional) has yet to be fully elucidated in the current era, and our survey results confirm this notion as only half of respondents participate in simulation-based continuing education training for E-CPR.…”
Section: Discussionmentioning
confidence: 99%
“…117 We also found very-lowquality evidence (downgraded for risk of bias, inconsistency, indirectness, and imprecision) from 2 observational studies. 118,119 For the important outcome of skill performance at 4 months to 1 year (patient tasks), we found very-low-quality evidence (downgraded for risk of bias, inconsistency, and imprecision) from 2 randomized trials 110,120 that showed that team or leadership training improved CPR hands-on time and time to initiation of various patient tasks at follow-up assessment.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…Several subsequent reports from different centers around the world have followed a similar model, in which a rapid response team (RaRT) is alerted in the setting of cardiac arrest or emergent cannulation [40,41,42•, 43••, 44•]. The members of the RaRT have predefined roles and generally train with medical simulation to improve performance [45]. Different institutions have different members as part of their RaRT (i.e., general surgeons, cardiac surgeons, ECMO nurses, respiratory technologists, intensivists, and perfusionists), but there is still variation in the immediate availability of team members, whether staff are in-house or on-call from home.…”
Section: Ecls Programs and Rapid Response Teamsmentioning
confidence: 99%
“…There is no doubt that the training for and an introduction of a rapid deployment system for ECMO will decrease times to institute ECPR and potentially improve survival [45]. Hence, if rapid deployment ECMO can reduce the period of minimal or no cardiac output and end-organ damage, then early mechanical support might improve outcomes.…”
Section: Rapid Deployment Versus Early Deploymentmentioning
confidence: 99%